Seroprevalence of Anti-SARS-CoV-2 Among Pregnant Women Prior to COVID-19 Vaccination in Pekanbaru, Riau (Future Science, 2022)
Pregnant women have higher risks for severe COVID-19. Therefore, this group requires protection, including in the form of vaccination. Generally, pregnant women are not included in the vaccine’s clinical trials, therefore safety data of COVID-19 vaccines for pregnant women are limited. As part of the safety and immunogenicity study of CoronaVac vaccine among pregnant women, we tested anti-S titer prior to vaccination. We recruited 45 women participating in the COVID-19 vaccination program. Only 3 of them (6.7%) reported having previous COVID-19 history. However, when tested for anti-S antibodies, more than half of the participants (26 persons, 57.8%) were reactive. Only one out of three participants reported previous COVID-19 infection was reactive for anti-S antibodies. Meanwhile, 25 (59.5%) of those who reported no previous infection were reactive. We found no factors influenced seropositivity, including gravida, gestational age, and healthcare profession. This high seropositivity among unvaccinated pregnant women who reported no previous infection reflected potential underreporting and underdetection of COVID-19 in the population.